The effectiveness of board game media in group guidance to improve career planning skills of vocational high school students: Systematic literature review - Imelda Dyah Rahmasari; Diniy Hidayatur Rahman; Zamroni Zamroni (Program Studi Bimbingan dan Konseling Islam IAIN Langsa, 2025)
Career planning is a key developmental competence for vocational high school students as they prepare for complex transitions from education to work. Yet many students still face difficulties in career exploration, decision-making, and goal setting because of limited self-awareness, inadequate career information, and conventional guidance practices. This systematic literature review synthesizes empirical evidence on the use of board game media in group guidance to improve vocational students’ career planning skills. Following the PRISMA 2020 framework, a systematic search was conducted in the Scopus database for peer-reviewed English-language articles published between 2015 and 2025. From 216 identified records, 36 studies met the inclusion criteria and were analyzed through narrative and convergent synthesis. Methodological quality was assessed using the Mixed Methods Appraisal Tool. The findings show that board game-based guidance supports career planning by strengthening career self-efficacy, decision-making skills, career maturity, motivation, and reflective engagement. Board games are especially useful when they integrate structured gameplay, peer interaction, facilitator-led debriefing, and culturally relevant career scenarios. However, the evidence remains limited by short intervention periods, heterogeneous outcome measures, insufficient effect-size reporting, and scarce longitudinal or randomized studies. Future research should employ stronger designs and standardized measures across diverse vocational education settings and cultural contexts.